(untitled) (Journal of Engineering, 2014)
The removal of heavy metal ions from wastewater by sorptive flotation using Amberlite IR120 as a resin, and flotation column, was investigated. A combined two-stage process is proposed as an alternative of the heavy metals removal from aqueous solutions. The first stage is the sorption of heavy metals onto Amberlite IR120 followed by dispersed-air flotation. The sorption of metal ions on the resin, depending on contact time, pH, resin dosage, and initial metal concentration was studied in batch method .Various parameters such as pH, air flow rate, and surfactant concentration were investigated in the flotation stage. Sodium lauryl sulfate (SLS) and Hexadecyltrimethyl ammonium bromide (HTAB) were used as anionic and cationic surfactant respectively. The sorption process, which is PH dependent, shows maximum removal of metal ions at pH 7. Langmuir and Freundlich isotherm expressions were found to give both a good fit to the experimental data. Kinetic data correlated well with Lagergren second order kinetic model, and flotation step enhanced the removal efficiency of nickel and cadmium from wastewater from about 75% to 94% and reduce turbidity so it can dispense with the filtering process, which is expensive technology. It is believed that flotation separation has great potential as a clean water and wastewater treatment technology.